Bacteriostatic and Bactericidal Profile of Leaves and Twigs Essential oils of Moroccan Pistacia lentiscus L. - Taoufik Haloui & , Abdellah Farah, Mounyr Balouiri, Marwa Chraibi, Mouhcine Fadil, Kawtar Fikri Benbrahim, Aziz Belrhiti Alaoui (Journal of Applied Pharmaceutical Science, 2015)
In order to increase the Moroccan Pistacia lentiscus L. value, the antibacterial activity of its twig’s and leave’s essential oils was evaluated. The study of antibacterial activity was performed on Gram positive bacteria Bacillus subtilis, Staphylococcus aureus and Gram-negative bacteria Escherichia coli, Pseudomonas aeruginosa by the microdilution method. The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) values of leaves and twigs essential oils against the four studied strains were determined and showed that both essential oils tested have remarkable antibacterial activity. Bacillus subtilis was the most sensitive strain against the two essential oils while Pseudomonas aeruginosa was the most resistant one.
Keywords: Essential oil, Pistacia lentiscus, antibacterial activity, bacteriostatic, bactericidal.